Hunger in Maine - Yellen, Donna; Swann, Mark; Schmidt, Elena (Maine Policy Review, 2011)
Hunger and food insecurity is on the rise in Maine. Mainers are experiencing a food emergency made graver by the economic recession and rising health costs. The authors of this article discuss hunger in Maine, focusing on private efforts to alleviate it.
Keywords: Maine; hunger; food assistance programs; food pantries